1959
DOI: 10.1302/0301-620x.41b1.4
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in Traction Lesions of the Brachial Plexus

Abstract: 1. Twenty-nine patients with traction lesions of the brachial plexus have been studied. 2. The methods of study have been by clinical examination, by operative exploration and biopsy and by examination of axon reflexes. 3. Results in each of these sections have been related to the progress of the lesions. 4. The results suggest: a) that the reason for the generally poor prognosis in traction lesions of the brachial plexus is the frequency of intradural preganglionic damage and of tearing apart of the plexus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

1970
1970
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(32 citation statements)
references
References 4 publications
0
28
0
4
Order By: Relevance
“…The finding of preserved peripheral sensory conduction in root avulsions of the brachial plexus was first described by Bonney and Gilliatt (1958) and has been confirmed by others (Warren et al, 1969;Buchthal et al, 1975).…”
Section: Methodsmentioning
confidence: 56%
“…The finding of preserved peripheral sensory conduction in root avulsions of the brachial plexus was first described by Bonney and Gilliatt (1958) and has been confirmed by others (Warren et al, 1969;Buchthal et al, 1975).…”
Section: Methodsmentioning
confidence: 56%
“…Following publication of this report, surgical repair of brachial plexus injuries was performed on a few occasions in the early 20 th century 3,4 with apparently good results, but the initial enthusiasm was replaced with pessimism because of the poor subsequent results 5,6 . In the early 1960s, the skepticism about the results from the surgical treatment was so intense that the treatment advocated for complete root avulsions was above-elbow amputation, combined with shoulder fusion in slight abduction and flexion, and complemented by a forearmhand prosthesis.…”
Section: Historymentioning
confidence: 99%
“…[5] Wrist and finger extension. [6] Wrist and finger flexion. [7] The ulnar innervated structures are the last priority because of the poor prognosis for recovery.…”
Section: Repair Prioritiesmentioning
confidence: 99%
“…Bonney (1959) followed 25 patients for a minimum of two years and found that the pain was worse in those who showed no functional recovery. Yeoman (1975) observed that severe pain persisted in 32 of his 46 patients with complete paralysis.…”
mentioning
confidence: 99%